A Simulation-Based Training Framework for Mine Rescue and Self-Escape Readiness - SME Annual Meeting 2025 - Muhammad Azeem Raza; Samuel Frimpong (Society for Mining, Metallurgy & Exploration, 2025)
Underground mining environments are inherently hazardous and can lead to emergencies where effective rescue and self-escape become critical. Missouri University of Science and Technology is pioneering new technologies for effective self-escape. The rescuers and miners need to be trained in these new technologically driven environments. Previous research in fields like aviation, medical surgery, and oil and gas drilling has demonstrated the effectiveness of virtual simulation training, but the mining sector has yet to fully adopt advanced tools such as eye-tracking and immersive training modules. This research proposes a comprehensive training infrastructure incorporating these technologies to enhance situational awareness and decision-making during emergencies. The novelty lies in the application of advanced miner escape and communication technologies, specifically designed to monitor and enhance cognitive responses in high-stress situations. By leveraging these technologies, the proposed training infrastructure aims to prepare the next generation of underground miners and operators, by equipping them with the necessary skills to manage emergencies effectively.